The Bank Vole (Clethrionomys glareolus) as a Model System for Adaptive Phylogeography in the European Theater - Kotlík, Petr; Marková, Silvia; Horníková, Michaela; Escalante, Marco A.; Searle, Jeremy B. (Frontiers in Ecology and Evolution, 2022)
The legacy of climatic changes during the Pleistocene glaciations allows inferences to be made about the patterns and processes associated with range expansion/colonization, including evolutionary adaptation. With the increasing availability of population genomic data, we have the opportunity to examine these questions in detail and in a variety of non-traditional model species. As an exemplar, here we review more than two decades of work by our group and others that illustrate the potential of a single “non-model model” mammal species - the bank vole (Clethrionomys glareolus), which is particularly well suited to illustrate the complexities that may be associated with range expansion and the power of genomics (and other datasets) to uncover them. We first summarize early phylogeographic work using mitochondrial DNA and then describe new phylogeographic insights gained from population genomic analysis of genome-wide SNP data to highlight the bank vole as one of the most compelling examples of a forest mammal, that survived in cryptic extra-Mediterranean (“northern”) glacial refugia in Europe, and as one of the species in which substantial replacement and mixing of lineages originating from different refugia occurred during end-glacial colonization. Our studies of bank vole hemoglobin structure and function, as well as our recent ecological niche modeling study examining differences among bank vole lineages, led us to develop the idea of “adaptive phylogeography.” This is what we call the study of the role of adaptive differences among populations in shaping phylogeographic patterns. Adaptive phylogeography provides a link between past population history and adaptation that can ultimately help predict the potential of future species responses to climate change. Because the bank vole is part of a community of organisms whose range has repeatedly contracted and then expanded in the past, what we learn from the bank vole will be useful for our understanding of a broad range of species.